Proceedings of the 2016 International Conference on Mathematics and Science Education 2017
DOI: 10.2991/icmsed-16.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

APPLYING THE qCOGNITIVE CONFLICTq STRATEGY TO FACILITATE CHANGES IN THE CONCEPTION OF FIRsT SEMESTER STUDENTS ON THE TOPIC OF VOLTAIC CELL

Abstract: Abstract-The main objective of this study was to obtain the information regarding freshman students' alternative conceptions, the characteristics of conflict cognitive strategy and the profile of students' conceptual change in Voltaic Cell, which were further elaborated into six determined indicators. The subject consisted of fourteen freshman students of Chemistry Programme. This study was conducted into three stages, which were (1)pre-test, (2)cognitive conflict instruction and (3) post-test. Students' conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Eliminating misconceptions is a difficult task. Studies show that misconceptions decrease but do not completely disappear (Chan, Burtis, & Bereiter, 1997;Güveli et al, 2022;Sumarna & Yulistiana, 2016). Efforts should be made not to eliminate misconceptions, but to prevent misconceptions from occurring.…”
Section: Discussion and Conclusion About Pretest Posttest Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eliminating misconceptions is a difficult task. Studies show that misconceptions decrease but do not completely disappear (Chan, Burtis, & Bereiter, 1997;Güveli et al, 2022;Sumarna & Yulistiana, 2016). Efforts should be made not to eliminate misconceptions, but to prevent misconceptions from occurring.…”
Section: Discussion and Conclusion About Pretest Posttest Resultsmentioning
confidence: 99%
“…The lack of self-confidence, decreased misconceptions, and increased scientific knowledge is positive outcomes of the CCA. Studies on CC (Akgün & Deryakulu, 2007;Chaw & David, 2013;Gökçe-Erdem, 2021;Güveli et al, 2022;Herawaty & Rusdi, 2016;Madu & Orji, 2015;Sumarna & Yulistiana, 2016;Yaman, 2013;Yılmaz, 2019) concluded that this method has a positive effect on conceptual change.…”
Section: Discussion and Conclusion About Pretest Posttest Resultsmentioning
confidence: 99%
See 1 more Smart Citation